Meiofauna Community in Soft Sediments at TAG and Snake Pit Hydrothermal Vent Fields - Spedicato, Adriana; Sánchez, Nuria; Pastor, Lucie; Menot, Lenaick; Zeppilli, Daniela (Frontiers in Marine Science, 2020)
The risk assessment of Seafloor Massive Sulfides (SMS) mining on meiobenthic organisms, specifically on soft-sediment meiofauna, is impeded by a lack of knowledge on the biology and ecology of these communities. In this study we investigated sediment samples taken in proximity of active vents at Trans-Atlantic Geotraverse (TAG) and Snake Pit, two hydrothermal vent fields of the Mid-Atlantic Ridge, in order to explore metazoan meiofauna, particularly nematode community, and its relation to organic carbon, total nitrogen, total sulfur and dissolved oxygen. Organic carbon and nitrogen contents were low at both sites. High concentrations of total sulfur and low oxygen penetration were found at Snake Pit compared to TAG. Snake Pit showed about four times higher meiofauna and nematode density compared to TAG, as well as a dissimilar nematode community composition. We hypothesize that high sulfur concentrations at Snake Pit may support high microbial growth, which represents one of the main food source for nematodes. Moreover, TAG nematode community mostly consisted of persisters (K-strategists), while Snake Pit one was composed by both persisters (Desmoscolecidae family) and colonizers (r-strategists Metalinhomoeus and Halomonhystera), whose presence can be facilitated by the bioturbation effect of polychaetes observed on the sediment surface. Therefore, food availability, geochemical settings and biotic interactions seem to drive the local meiofauna and nematode community. Our study also draws attention to the opportunity of including meiofauna and specifically nematodes in impact studies conducted in this area in order to assess and monitor the impact of SMS mining.